Utilización de Toxina Botulínica en el manejo de onfalocele gigante en un lactante. Informe de Caso - Salinas Barreto, Juan Jose (2021)
Introduction: Giant omphalocele is an abdominal wall defect of 5cm in diameter or more or presence of liver herniation. The use of botulinum toxin has been described as an adjunct therapy in the reconstruction of the abdominal wall in adults. Its use in pediatric patients is still little described but it does show safety and efficacy. Case Report: 40-week gestational-age female patient with a giant omphalocele with a wide defect measuring approximately 9 centimeters, in whom at 75 days of life botulinum toxin injections were applied around the defect and operated a week after for definitive abdominal wall closure which was achieved without tension or post-operative intercurrences. Conclusion: The use of botulinum toxin is shown to be highly effective in achieving abdominal wall closure in infant patients with giant omphalocele.